2013
DOI: 10.1042/bj20121256
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols differentially inhibit degranulation of distinct subsets of vesicles in mast cells by specific interaction with granule-type-dependent SNARE complexes

Abstract: Anti-allergic effects of dietary polyphenols were extensively studied in numerous allergic disease models, but the molecular mechanisms of anti-allergic effects by polyphenols remain poorly understood. In the present study, we show that the release of granular cargo molecules, contained in distinct subsets of granules of mast cells, is specifically mediated by two sets of SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins, and that various polyphenols differentially inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 47 publications
0
33
0
2
Order By: Relevance
“…Alternatively, there may be differential inhibition of gene expression, involving the inhibition of nuclear transcription targets (NF-KB or STAT), compared with cytokine or chemokine protein secretion. Instead, mediator trafficking and secretion may involve inhibition of specific target proteins involved in vesicle fusion, such as soluble N-ethylmaleimide-sensitive factor attachment protein complexes (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, there may be differential inhibition of gene expression, involving the inhibition of nuclear transcription targets (NF-KB or STAT), compared with cytokine or chemokine protein secretion. Instead, mediator trafficking and secretion may involve inhibition of specific target proteins involved in vesicle fusion, such as soluble N-ethylmaleimide-sensitive factor attachment protein complexes (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…A potential mechanism of selectivity of flavonoids, where luteolin was the best inhibitor of histamine and β-hex release, may be disruption of distinct MC vesicle secretion by interacting with granule-dependent SNARE complexes. 64 Interestingly, the beneficial action of cromolyn may also not to be selective for MC as it could be mediated through inhibition of sensory nerve endings, recently shown for a cromolyn containing skin cream. 27 Other studies have shown that cromolyn may stimulate afferent nerves in humans.…”
Section: Discussionmentioning
confidence: 99%
“…VAMP8 can control various stages of granule-mediated secretion. Mast cells undergo piecemeal degranulation, which is regulated through the VAMP8 and VAMP7 as R-SNAREs located on secretory granules and Stx4/SNAP23 on the cell surface [92,96,[98][99][100]. In pancreatic acinar cells VAMP8 regulates granule-to-granule, but not granule-to-surface, fusion during compound exocytosis, whether this is the case for mast cell is unclear [101].…”
Section: Tnf Secretion From Mast Cellsmentioning
confidence: 96%